PENYUSUNAN MODEL PENGELOLAAN KUALITAS TANAH SAWAH DI KECAMATAN JATIPURO KABUPATEN KARANGANYAR - Wahyu Adi Nugroho; Sudjono Utomo; Widyatmani Sih Dewi (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2011)
Title : Paddy Soil Quality Management Modeling in District of Jatipuro, Karanganyar Regency. The intensive paddy soil management were known caused the soil degradation, thus the proper paddy soil quality management was needed to maintain the sustainability of soil function. The aim of the research was built a model that can be used as the reference of paddy soil quality management in district of Jatipuro, Karanganyar regency. The research was executed on October 2008 until February 2009. The research was descriptive explorative, carried out by collecting secondary data for model building and getting sample based on random sampling method at paddy soil in each Soil Map Unit (SMU), laboratory analysis for each selected soil quality indicator, and field observation for model validation. The results showed that the builded model: SQi = 0,414 + 0,363 pH, can be used as the reference of paddy soil quality management in district of Jatipuro. Based on the model then the recommendation of paddy soil quality management could be determined, through increasing pH by submerged the soil and delay the rice planting about 2 weeks after flooding. Keywords: model, paddy soil quality, district of Jatipuro